ANALISIS KESANTUNAN CERITA RAKYAT ANDHE-ANDHE LUMUT KARYA SUNJAYA DAN KAITANNYA DENGAN PEMBELAJARAN APRESIASI SASTRA JAWA - Wardani, Herlina Kusuma; Suhita, Raheni; Suryanto, Edy (Universitas Sebelas Maret, 2019)
This research aims to describe and explain: (1) the form of politeness in speech act within Andhe-Andhe Lumut Folklore by Sunjaya: and (2) relevance of Andhe-Andhe Lumut Folklore by Sunjaya as a teaching material for 7th Grade Junior High Student s in order to understand a folklore itself. The writer uses documents and some informants as the research’s data sources. Purposive sampling is usedto determine the sample used in this research, while data collection is done by using interview and documents analysis techniques. In this research, the writer uses data source triangulation and politeness theory to test the validity of collected data. In analysis part, the writer uses interactive data analysis which consists of data collection, data reduction, data presenting and concluding remark stages. As for the results of this study, the writer find that: (1) In the folklore story book of ‘Andhe-Andhe Lumut written by Sunjaya, it is found that politeness takes form in both assertive, directive and expressive speech acts, with directive speech acts being the most common one. The directive speech act is regularly used in the folklore, because most of the utterances (statements) found in the story are asking for a response. (2) It can be concluded that Andhe-Andhe Lumut Folklore by Sunjaya is a relevant teaching material to understand a folklore story for 7th grade Junior High School students based on the folklore’s curriculum, languages, psychological and cultural aspect. First, according to the Junior High School Curriculums of 2013, it is stated that understanding folklore is one of the basic competences that should have been mastered in the first semester of 7th grade students. Secondly, Andhe-Andhe Lumut by Sunjaya uses a polite language that can be a good example for the students to learn to use a polite and proper Javanese Language in their daily lives. Thirdly, in terms of psychological aspects, the story is suitable with the mental development of 7th grader students. And finally, the story shared a similar cultural background with its readers who areJavanese, so it is highly relevant and related with the readers’ values.